Acceptability of the "Love, Sex, & Choices" HIV Prevention Intervention by Hispanic Female College Students. (June 2021) - Jones, Sandra Gracia; Jones, Rachel; Fenkl, Eric A.; Lacroix-Williams, Lorraine; Simon, Sharon; Chadwell, Katherine
Introduction: Hispanic women are affected by HIV. "Love, Sex & Choices" (LSC) is an innovative 12-episode urban soap opera video series targeting young adult Black women streamed to smartphones. This study purpose was to determine whether LSC is an acceptable HIV prevention intervention for female Hispanic college students in South Florida. Method: After institutional review board approval, female Hispanic college students were recruited from two campuses to watch the LSC video series and complete an online evaluation survey. Results: Study participants ( n =101) evaluated LSC as definitely/probably important for women (97.0%), helpful for making relationship decisions (86.2%), changing attitudes about having sex (79.2%), asking partners to use a condom (80.2%), leaving partners who won't use condoms (74.2%), handling oneself in tough situations in a relationship (79.2%), and getting an HIV test (83.2%). Participants liked/related to LSC and thought their friends would also like the series. Conclusions: Results indicated that young Hispanic women related to the video series, were likely to get HIV tested after watching the video series, found the story lines realistic, and thought their friends would like the series. The next step is to test the effectiveness of LSC to change behaviors of young Hispanic women at risk of HIV.